Influence of model environment complexity on corrosion mechanism of biodegradable zinc alloys. (15th July 2021) - Hybasek, Vojtech; Kubasek, Jiri; Capek, Jaroslav; Alferi, Dino; Pinc, Jan; Jiru, Jitrenka; Fojt, Jaroslav
Highlights: A corrosion-limiting barrier is formed in all used media. The barrier layer formed in SBF does not correspond to in-vivo data. The natural-like barrier containing zinc phosphate is formed in MEM. Serum proteins block corrosion-preffered sites. Abstract: Today, many biodegradable zinc alloys are being developed. Thus, it is necessary to have a corrosion test enabling the selection of alloys already in development laboratories. However, the results must agree with the data from in-vivo . In this work, the complexity of available models of the body environment on the mechanism of the degradation of the Zn-0.8Mg-0.2Sr was studied. The tested media were physiological saline, simulated body fluid, and minimal essential medium with or without proteins. The natural-like barrier is formed in MEM. Proteins block less noble sites. The response in the first hours of exposure differs from longer-term data.